(untitled) (Bangladesh Journal of Zoology, 2024)
This research looks at the biochemical makeup of the edible gastropod Pila globosa, which is found in freshwater. One of Bangladesh’s largest beels, Chalan Beel, is where this investigation was conducted for analyze the nutritional value of this snail. In freshwater snails, seasonal variations in biochemical composition, including protein, fat, and ash, have been observed during two distinct periods: the Active period and the Aestivation period. On body meat, this analysis was conducted. The Micro-Kjeldahl distillation method was used to evaluate the protein content. There were no seasonal variations in the body’s edible water content. Significant seasonal fluctuations were seen in other edible portion components, though. It was discovered that throughout both the active and aestivation periods, the edible portions had a high protein proportion. The range of the calorific value (including ash) was 7.83 to 11.98%. Seasonal variations were seen in the edible body part’s fat and carbohydrate composition. It was discovered that throughout both the active and aestivation periods, the edible portions had a high protein proportion which can help to alleviate nutrient deficiencies. Bangladesh J. Zool. 52(2): 263-270, 2024